The contract of marriage and its purposes from Islamic perspective - Laluddin, Hayatullah; Abdul Manap, Norhoneydayatie; Mohd. Shariff, Ahmad Azam; Muhammad Husni, Ahmad; Mohd. Kusrin, Zuliza; Ibrahim, Ibnor Azli; Abdul Manap, Nazura (Canadian Center of Science and Education, 2014)
The prosperity and success of a society heavily depends on the strength of the relation of its individual members, thus family constituting the fundamental unit of the structure of society provides the avenue for initiation of such relation among the individual members. Marriage as the only process through which families are brought into existence can play a very significant role in formulation of a good and cordial relation between individual at the micro level in the society hence, extending it to macro level. Therefore, this paper attempts to delineate on the significance of marriage in Islam, its purposes and role, in creation of cordial relation among the members of the society. This paper using an analytical method concludes that marriage leads to formation of cordial relation among family members hence result an integrated social relation network in the society